Multisource feedback to assess pediatric practice: a systematic review - Al Alawi, Samah; Al Ansari, Ahmed; Raees, Ayman; Al Khalifa, Salman (Revue canadienne de l'éducation médicale, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> Introduction: The assessment and maintenance of competence for pediatricians has recently received increased attention. The aim of the present study was to investigate further the use of multisource feedback for assessing pediatricians in practice. Methods: A systematic literature review was conducted using the electronic databases EMBASE, PsycINFO, MEDLINE, PUBMED, and CINAHL for English-language articles. Results: 762 articles were identified with the initial search and 756 articles were excluded for a total of six studies that met the inclusion criteria for this systematic review. Internal consistency reliability was reported in five studies with α > 0.95 for both subscales and full scales. Generalizability was also reported in two studies with Ep2 generally > 0.78. These adequate Ep2 coefficients were achieved with different numbers of raters. Evidence for content, criterion-related (e.g., Pearson’s r) and construct validity (e.g., principal component factor analysis) was reported in all 6 studies. Conclusion: Multisource feedback is a feasible, reliable, and valid method to assess pediatricians in practice. The results indicate that multisource feedback system can be used to assess key competencies such as communication skills, interpersonal skills, collegiality, and medical expertise. Further implementation of multisource feedback is desirable. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->